High-strength low-elongation chinlon 66 carbon black master batch as well as preparation method and application thereof

By combining modified superdispersants and high-temperature resistant antioxidants, the dispersant ratio and process were optimized, solving the problems of uneven dispersion and oxidative degradation of nylon 66 carbon black masterbatch at high temperatures. This improved the fiber's breaking strength and elongation, ensuring the stability of the spinning process.

CN120944345APending Publication Date: 2025-11-14FUJIAN EVERSUN JINJIANG CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511154626.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-18
Publication Date
2025-11-14

AI Technical Summary

Technical Problem

Existing nylon 66 carbon black masterbatch is prone to carbon black particle agglomeration at high temperatures, resulting in decreased fiber breaking strength and increased breaking elongation. The proportion of dispersant addition lacks scientific quantification. Polyamide 66 masterbatch is easily oxidized and degraded at high temperatures, affecting fiber quality.

Method used

By using modified superdispersants and high-temperature resistant antioxidants, optimizing the type and ratio of dispersants, and combining with the modification process, high-strength, low-elongation nylon 66 carbon black masterbatch was prepared. It was produced by a twin-screw extruder to control the dispersion effect under high-temperature conditions.

Benefits of technology

It significantly improves carbon black dispersion, enhances fiber mechanical properties, increases the breaking strength of nylon 66 black yarn and reduces breaking elongation, thereby increasing the stability and high-temperature adaptability of the spinning process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120944345A_ABST
    Figure CN120944345A_ABST
Patent Text Reader

Abstract

The invention discloses a high-strength low-elongation chinlon 66 carbon black master batch as well as a preparation method and spinning application thereof. The high-strength low-elongation chinlon 66 carbon black master batch comprises the following raw materials: 68.2-68.8% of polyamide 66 slices, 30% of nano carbon black, 1-1.5% of a single modified hyperdispersant and 0.2-0.3% of a high-temperature-resistant antioxidant. The preparation process comprises the steps of material preparation, melting and plasticizing, screw shearing, water-cooling pelletizing, screening and drying and the like. According to the master batch, by optimizing the formula of the dispersing agent and the antioxidant, the problems of carbon black agglomeration and polyamide thermal oxidation degradation are effectively solved, the breaking strength of the chinlon 66 black yarn is remarkably improved, the elongation at break is reduced, the service life of a spinning assembly is prolonged, the end breakage rate is reduced, and the blackness is improved. The master batch has the characteristics of stable process and excellent performance in spinning application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of chemical fiber materials technology, specifically relating to a high-strength, low-elongation nylon 66 carbon black masterbatch, its preparation method, and its application. Background Technology

[0002] Nylon 66, also known as polyamide 66 (PA66), is a high-performance chemical fiber with good abrasion resistance and heat resistance, holding an important position in the industrial textile field. In actual production, to adapt to more application scenarios, it requires dyeing. Solution dyeing is a green and environmentally friendly method for producing colored fibers because it avoids the large amounts of wastewater generated during dyeing and finishing. Among many colored fibers, black is the primary demand due to its wider range of applications, and its production generally relies on the addition of carbon black masterbatch for coloring. Currently, carbon black masterbatch is mainly produced by blending polyamide 66 chips, nano-sized carbon black powder, and dispersants using a twin-screw extruder in a certain proportion, typically employing conventional dispersant systems such as fatty acid salts and polyethylene wax.

[0003] Nylon 66 requires a relatively high spinning temperature, typically reaching 280–300°C. If the dispersant is not selected properly, the increased thermal motion of the molecular chains can lead to the dynamic migration of carbon black particles and the formation of local agglomerates. This results in a decrease in the breaking strength and an increase in the breaking elongation of the final nylon 66 black yarn, severely restricting the production of high-quality black nylon 66 fiber.

[0004] Besides the choice of dispersant, the proportion of dispersant added also affects the final physical properties of nylon 66 black yarn. Existing patented dispersants generally adopt an empirical addition range of 3%-8%, but the addition ratio lacks scientific quantitative basis and does not consider the influence of carbon black specific surface area on the amount of dispersant used. When added in excess, the dispersant molecules will weaken the entanglement between nylon 66 molecular chains, resulting in a decrease in fiber modulus.

[0005] Currently, most polyamide 66 masterbatch production uses twin-screw extruders for blending and pelletizing, which cannot completely isolate oxygen during the process. Because polyamide 66 has a higher melting point, the required production temperature is also higher than that of common polyamide 6. However, polyamide 66 is more prone to oxidative degradation at high temperatures, further leading to a decline in the quality of polyamide 66 masterbatch. This results in significantly lower tensile strength and significantly higher elongation at break in downstream nylon 66 black yarn.

[0006] Currently, methods to reduce the breaking elongation and improve the strength of nylon 66 black yarn generally include the following two: First, increasing the draw ratio during spinning to fully stretch the fiber by utilizing the difference in guide roller speeds. This method has certain limitations. Firstly, the draw ratio cannot be increased indefinitely; an excessively high draw ratio will lead to excessive tension during spinning, causing yarn breakage and making production impossible. Second, modifying the yarn with masterbatches containing hydrogen bonds to increase the intermolecular forces. However, the addition of other masterbatches can cause changes in fiber color, increasing instability in continuous production. Furthermore, nylon 66 black yarn already contains a significant amount of carbon black nanoparticles; introducing too many other materials will further reduce the fiber's spinnability and shorten the spinning cycle.

[0007] CN113321929A discloses a carbon black masterbatch for nylon 6 civilian filament fibers. The weight percentages of the components in the carbon black masterbatch are: 57-79% polyamide 6 chips, 20-40% nano-sized carbon black powder, and 1-3% single-type carbon black superdispersant powder. This invention effectively solves the problem of uneven yarn and increased fuzz caused by spinning vibration due to spinneret wear in the later stages of long-cycle spinning production. However, it cannot solve the problems of high temperature and carbon black agglomeration. Furthermore, the superdispersant 330 used in this invention is an unmodified dispersant with a relatively low branched content. Because polyamide 66 has a higher viscosity, the dispersion effect is not ideal when using dispersant 330 in the production of polyamide 66 masterbatch. Polyamide 66 has a higher granulation and spinning temperature than the widely used polyamide 6, exhibiting excellent heat resistance and abrasion resistance, and is better suited to the changing outdoor environment.

[0008] Taking all the above factors into consideration, selecting a modified and suitable dispersant during the production of polyamide 66 carbon black masterbatch can reduce the agglomeration of carbon black nanoparticles. Simultaneously, the addition of a high-temperature resistant antioxidant can, to some extent, improve the breaking strength of nylon 66 black yarn and reduce its elongation at break. Based on this, combined with masterbatch modification and process optimization, it is expected to further facilitate the market promotion of nylon 66. Summary of the Invention

[0009] To address the problems existing in the prior art, this invention provides a high-strength, low-elongation nylon 66 carbon black masterbatch, its preparation method, and its application. By optimizing the type and ratio of dispersant and adding a high-temperature resistant antioxidant, the dispersibility of carbon black is significantly improved, thus enhancing the mechanical properties of the fiber. The preparation method includes premixing and twin-screw extrusion steps, ensuring a stable process.

[0010] To achieve the above objectives, the present invention provides the following technical solution: One of the objectives of this invention is to provide a high-strength, low-elongation nylon 66 carbon black masterbatch, comprising the following components by weight percentage: 68.2-68.8% polyamide 66 chips, 30% nano-sized carbon black powder, 1-1.5% single-type modified superdispersant, and 0.2-0.3% high-temperature resistant antioxidant.

[0011] Further, the polyamide 66 chips are one of the following: glossy polyamide 66 chips (titanium dioxide content ≤ 0.05%), semi-matte polyamide 66 chips (titanium dioxide content in the range of 0.1 to 0.6%), or fully matte polyamide 66 chips (titanium dioxide content ≥ 1.2%).

[0012] Furthermore, the polyamide 66 chips have a water content of 600–1000 ppm, an extractable content of ≤ 0.3%, a molecular weight of 18000–28000, and a relative viscosity range of 2.45–2.70.

[0013] Furthermore, the nano-sized carbon black powder has a particle size of 30–50 nm and an oil absorption value ≤ 70 cm⁻¹. 3 / 100g, purity ≥99.99%.

[0014] Furthermore, the single-type modified superdispersant is a polyamide dispersant with more branched chains and functional groups, a melting point in the range of 140-160℃, and a thermal decomposition degree of ≤97% at 300℃.

[0015] Furthermore, the high-temperature resistant antioxidant is a compound of S9228 antioxidant and A30 antioxidant, wherein the compounding ratio is A30:S9228, (1~2):1.

[0016] The second objective of this invention is to provide a method for preparing nylon 66 carbon black masterbatch, comprising the following steps: S1. Premix nano-sized carbon black powder with a single type of modified superdispersant to obtain a uniform mixture; S2. The polyamide 66 chips are automatically fed through the main feed port at a set flow rate; the mixture from step S1 is fed through the side feed port at a set flow rate. S3, the mixture, and polyamide 66 chips were sequentially processed in a parallel co-rotating twin-screw extruder through melt plasticization, screw conveying and shearing, water-cooled pelletizing, vibration screening, and forced-air drying to prepare high-strength, low-elongation nylon 66 carbon black masterbatch.

[0017] The high-strength, low-elongation nylon 66 carbon black masterbatch obtained through the above steps has a moisture content of 600–800 ppm and a relative viscosity of 2.20–2.24.

[0018] Furthermore, the melting and plasticizing process in step S2 is divided into eleven temperature zones and a die head temperature zone, with the temperature controlled within the range of 250 to 280°C. The temperature control for each section is as follows: Section 1: 265℃; Section 2: 275℃; Section 3: 275℃; Section 4: 275℃; Section 5: 270℃; Section 6: 265℃; Section 7: 260℃; Section 8: 255℃; Section 9: 250℃; Section 10: 245℃; Section 11: 240℃; Head unit: 275℃. The third objective of this invention is to provide an application of nylon 66 carbon black masterbatch in black yarn spinning. The high-strength, low-elongation nylon 66 carbon black masterbatch is melt-blended with polyamide 66 semi-dull chips and then used for nylon 66 black yarn spinning. The addition amount of high-strength, low-elongation nylon 66 carbon black masterbatch is 5%, the addition amount of polyamide 66 semi-dull chips is 95%, the spinning temperature is 280-300℃, the die temperature is 280-295℃, and the draw ratio is 1.3-1.6. The spinning screw is divided into 5 temperature zones, which are as follows from the feed end to the extrusion end: 285~290℃, 290~300℃, 285~300℃, 285~295℃, and 280~295℃.

[0019] Compared with the prior art, the advantages and beneficial effects of the present invention are as follows: 1. The improved dispersant used in this invention for preparing nylon 66 carbon black masterbatch utilizes a polyamide dispersant containing fatty acid groups. This dispersant shares the same long-chain polyamide structure as polyamide 66, enabling better bonding with the matrix. Furthermore, the dispersant structure contains more long-chain fatty acid branches and functional groups than conventional superdispersants, increasing steric hindrance and achieving multi-point anchoring and three-dimensional protection. This is more conducive to intermolecular dispersion, especially under extreme conditions (such as high temperature and high ion concentration), thus reducing the final amount of dispersant used in the formulation, improving spinning conditions, and further reducing filament drift and breakage during spinning. Simultaneously, the structure of the dispersant increases its overall molecular weight, raising its melting point to around 160℃, enhancing thermal stability (≤97% thermal decomposition at 300℃), making it more suitable for the high-temperature environment of nylon 66 carbon black masterbatch production. The dispersant's melting point is lower than that of polyamide 66 chips, allowing for better pre-melting and ideal dispersion. Meanwhile, the high proportion of long fatty acid chains in the dispersant also gives it a certain degree of hydrophobicity, which to some extent alleviates the risk of ring blockage caused by water absorption in nylon 66 carbon black masterbatch during spinning, and increases the stability of continuous production.

[0020] 2. In this invention, polyamide 66 chips are selected as the main base material for carbon black masterbatch. As one of the high-end fibers on the market, polyamide 66 has excellent heat resistance and wear resistance, and is not easily brittle at low temperatures, which can better meet the needs of outdoor variable environments. The beneficial effects of the carbon black masterbatch for nylon 66 prepared by this invention are basically unaffected by titanium dioxide and can be applied to various scenarios.

[0021] 3. The preferred particle size of this invention is 30–50 nm, and the oil absorption value is ≤ 70 cm⁻¹. 3 / 100g of carbon black with a purity of ≥ 99.99% is used as the raw material for coloring. This carbon black has a low particle size and a low oil absorption value. Carbon black with a low oil absorption value has the characteristics of loose structure, low degree of particle aggregation, and good dispersibility, which makes its processing performance better and energy consumption lower. To a certain extent, it improves the dispersibility of nylon 66 carbon black masterbatch.

[0022] 4. The black yarn produced by the present invention is made by blending the obtained nylon 66 carbon black masterbatch with polyamide 66 chips and spinning. Under this formula and ratio, the nylon 66 black yarn retains high breaking strength and suitable breaking elongation. Attached Figure Description

[0023] Figure 1 This is a photograph of the carbon black masterbatch for nylon 66 prepared according to the present invention. Figure 2 This is an infrared comparison image of the dispersant used in this invention and the polyether ester superdispersant 330 in the prior art. Detailed Implementation

[0024] The present invention will be further described below with reference to preferred embodiments and the accompanying drawings. The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values; these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and individual point values, and individual point values ​​can be combined to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein. Unless otherwise specified, the materials, reagents, etc., used in the following embodiments are commercially available. Unless otherwise specified, the experimental methods in the following embodiments are conventional methods.

[0025] The polyamide 66 chips used in the following examples have a water content of 600–1000 ppm, extractable content ≤0.3%, molecular weight of 18,000–28,000, and relative viscosity range of 2.45–2.70.

[0026] The nanoscale carbon black powder used in the following examples has a particle size range of 30–50 nm and an oil absorption value ≤70 cm⁻¹.3 / 100g, purity ≥99.99%.

[0027] The single-type modified dispersant used in the following examples is model ABX01. This dispersant is a polyamide dispersant with more branched chains and functional groups, a melting point in the range of 140 to 160°C, and a thermal decomposition degree of ≤97% at 300°C.

[0028] The high-temperature resistant antioxidants used in the following examples are a mixture of A30 antioxidant and S9228 antioxidant, wherein the mixing ratio is A30:S9228, (1~2):1.

[0029] Example 1 This embodiment provides a high-strength, low-elongation nylon 66 carbon black masterbatch, comprising the following components by weight percentage: 68.5% semi-dull polyamide 66 chips (titanium dioxide content in the range of 0.1-0.6%), 30.0% nano-sized carbon black powder, 1.2% single-type modified superdispersant, and 0.3% high-temperature resistant antioxidant.

[0030] The preparation method of carbon black masterbatch for nylon 66 specifically includes the following steps: S1. 30.0% of the particles have a diameter range of 30–50 nm and an oil absorption value ≤70 cm⁻¹. 3 A mixture is obtained by premixing 100g of nano-sized carbon black powder, 1.2% of a single-type modified superdispersant and 0.3% of a high-temperature resistant antioxidant. S2. 68.5% of fiber-grade semi-dull polyamide 66 chips with a diameter of 2.0 mm and a height of 3.0 mm are added to the main feed position of a parallel co-rotating twin-screw extruder granulator via a loss-in-weight weighing automatic feeding method, with the main feed speed controlled at 25 Hz; the mixture obtained in step S1 is added to the side feed position of the parallel co-rotating twin-screw extruder granulator via a loss-in-weight weighing automatic feeding method, with the side feed speed controlled at 25 Hz; S3, the mixture, and polyamide 66 chips were sequentially melt-plasticized in a parallel co-rotating twin-screw extruder. The melt-plasticization process was divided into eleven temperature zones and a die head temperature zone. The temperature control of each zone was as follows: Zone 1: 265℃; Zone 2: 275℃; Zone 3: 275℃; Zone 4: 275℃; Zone 5: 270℃; Zone 6: 265℃; Zone 7: 260℃; Zone 8: 255℃; Zone 9: 250℃; Zone 10: 245℃; Zone 11: 240℃; Die head: 275℃; Screw transmission and shearing: The main speed of the screw transmission and shearing machine was 500 r / min; Water-cooled pelletizing: The main speed of the water-cooled pelletizer was 550 r / min; Vibration screening: The screen mesh diameter of the vibration screening machine was 4 mm; Blow-air drying: A high-strength, low-elongation nylon 66 carbon black masterbatch with a moisture content of 800 ppm and a relative viscosity of 2.20 was prepared, denoted as polyamide 66 carbon black masterbatch-1.

[0031] Example 2 This embodiment provides a high-strength, low-elongation nylon 66 carbon black masterbatch, comprising the following components by weight percentage: 68.8% bright polyamide 66 chips (titanium dioxide content ≤0.05%), 30.0% nano-sized carbon black powder, 1% single-type modified superdispersant, and 0.2% high-temperature resistant antioxidant.

[0032] The preparation method of carbon black masterbatch for nylon 66 specifically includes the following steps: S1. 30.0% of the particles have a diameter range of 30–50 nm and an oil absorption value ≤70 cm⁻¹. 3 A mixture is obtained by premixing 100g of nano-sized carbon black powder, 1% of a single-type modified superdispersant, and 0.2% of a high-temperature resistant antioxidant. S2. 68.8% of fiber-grade bright polyamide 66 chips with a diameter of 2.0 mm and a height of 3.0 mm are added to the main feed position of a parallel co-rotating twin-screw extruder granulator via an automatic feeding method using a loss-in-weight weighing system, with the main feed speed controlled at 25 Hz; the mixture obtained in step S1 is added to the side feed position of the parallel co-rotating twin-screw extruder granulator via an automatic feeding method using a loss-in-weight weighing system, with the side feed speed controlled at 25 Hz; S3, the mixture, and polyamide 66 chips were sequentially melt-plasticized in a parallel co-rotating twin-screw extruder, with temperature control in each zone as described in Example 1; Screw conveying and shearing: the main speed of the screw conveying and shearing machine was 500 r / min; Water-cooled pelletizing: the main speed of the water-cooled pelletizer was 550 r / min; Vibration screening: the screen mesh diameter of the vibration screening machine was 4 mm; Blow-air drying: a high-strength, low-elongation nylon 66 carbon black masterbatch with a moisture content of 700 ppm and a relative viscosity of 2.215 was prepared, denoted as polyamide 66 carbon black masterbatch-2.

[0033] Example 3 This embodiment provides a high-strength, low-elongation nylon 66 carbon black masterbatch, comprising the following components by weight percentage: 68.3% matte polyamide 66 chips (titanium dioxide content ≥1.2%), 30.0% nano-sized carbon black powder, 1.5% single-type modified superdispersant, and 0.2% high-temperature resistant antioxidant.

[0034] The preparation method of carbon black masterbatch for nylon 66 specifically includes the following steps: S1. 30.0% of the particles have a diameter range of 30–50 nm and an oil absorption value ≤70 cm⁻¹. 3 A mixture is obtained by premixing 100g of nano-sized carbon black powder, 1.5% of a single-type modified superdispersant, and 0.2% of a high-temperature resistant antioxidant. S2. 68.3% of fiber-grade bright polyamide 66 chips with a diameter of 2.0 mm and a height of 3.0 mm are added to the main feed position of a parallel co-rotating twin-screw extruder granulator via a loss-in-weight weighing automatic feeding method, and the main feed speed is controlled at 25 Hz; the mixture obtained in step (1) is added to the side feed position of the parallel co-rotating twin-screw extruder granulator via a loss-in-weight weighing automatic feeding method, and the side feed speed is controlled at 25 Hz; S3, the mixture, and polyamide 66 chips were sequentially melt-plasticized in a parallel co-rotating twin-screw extruder, with temperature control in each zone as described in Example 1; Screw conveying and shearing: the main speed of the screw conveying and shearing machine was 500 r / min; Water-cooled pelletizing: the main speed of the water-cooled pelletizer was 550 r / min; Vibration screening: the screen mesh diameter of the vibration screening machine was 4 mm; Blow-air drying: a high-strength, low-elongation nylon 66 carbon black masterbatch with a moisture content of 600 ppm and a relative viscosity of 2.236 was prepared, denoted as polyamide 66 carbon black masterbatch-3.

[0035] Example 4 Using the high-strength, low-elongation nylon 66 carbon black masterbatch produced in Example 1 as raw material, 5% of the high-strength, low-elongation nylon 66 carbon black masterbatch and 95% of semi-dull polyamide 66 chips were mixed for nylon 66 black yarn spinning. The spinning screw was divided into 5 temperature zones, from the feed end to the extrusion end: 285℃, 295℃, 292℃, 290℃, 285℃, with the die temperature at 285℃ and the draw ratio controlled at 1.6. The yarn finally produced was denoted as Nylon 66 Black Yarn-1.

[0036] Example 5 In this embodiment, the polyamide 66 carbon black masterbatch-2 prepared in Example 2 was used for black yarn spinning. The black yarn spinning process conditions were the same as in Example 4, and the resulting yarn was denoted as nylon 66 black yarn-2.

[0037] Example 6 In this embodiment, the polyamide 66 carbon black masterbatch-2 prepared in Example 3 was used for black yarn spinning. The black yarn spinning process conditions were the same as in Example 4, and the resulting yarn was denoted as nylon 66 black yarn-3.

[0038] Comparative Example 1 This embodiment provides a nylon 66 carbon black masterbatch, which includes the following raw materials by weight percentage: 67% semi-glossy polyamide 66 chips, 30.0% nano-sized carbon black powder, and 3.0% single-type modified superdispersant.

[0039] The modified superdispersant content in the nylon 66 carbon black masterbatch provided in this embodiment is too high, which leads to a reduction in screw shearing action and high-frequency intermittent strand breakage during extrusion. This causes production abnormalities and makes it impossible to stably produce nylon 66 carbon black masterbatch. The obtained masterbatch is denoted as polyamide 66 carbon black masterbatch-4, and the yarn produced by spinning it is denoted as nylon 66 black yarn-4.

[0040] Comparative Example 2 This embodiment provides a nylon 66 carbon black masterbatch, comprising the following raw materials by weight percentage: 70% semi-glossy polyamide 66 chips and 30.0% nano-sized carbon black powder. Due to the lack of a dispersant, the mixing effect between the carbon black powder and polyamide 66 is poor and uneven, resulting in high-frequency intermittent strand breakage during extrusion, causing production abnormalities and making it impossible to stably produce nylon 66 carbon black masterbatch.

[0041] Comparative Example 3 The nylon 66 carbon black masterbatch comprises the following components by weight percentage: 69.0% polyamide 66 bright chips, 30.0% nano-sized carbon black powder, and 1.0% single-type modified superdispersant. The masterbatch production process is the same as in Example 1, and is designated as polyamide 66 carbon black masterbatch-5. The yarn produced using the polyamide 66 carbon black masterbatch-5 provided in the comparative example is designated as nylon 66 black yarn-5.

[0042] Comparative Example 4 The nylon 66 carbon black masterbatch comprises the following components by weight percentage: 68.9% polyamide 66 semi-dull chips, 30.0% nano-sized carbon black powder, and 1.1% single-type superdispersant. The masterbatch production process is the same as in Example 1, and is designated as polyamide 66 carbon black masterbatch-6. The yarn produced using the polyamide 66 carbon black masterbatch-6 provided in the comparative example is designated as nylon 66 black yarn-6.

[0043] Comparative Example 5 The nylon 66 carbon black masterbatch comprises the following components by weight percentage: 68.8% polyamide 66 semi-dull chips, 30.0% nano-sized carbon black powder, and 1.2% single-type superdispersant. The masterbatch production process is the same as in Example 1, and is designated as polyamide 66 carbon black masterbatch-7. The yarn produced using the polyamide 66 carbon black masterbatch-7 provided in the comparative example is designated as nylon 66 black yarn-7.

[0044] Comparative Example 6 The nylon 66 carbon black masterbatch comprises the following components by weight percentage: 68.5% polyamide 66 semi-dull chips, 30.0% nano-sized carbon black powder, and 1.5% single-type superdispersant. The masterbatch production process is the same as in Example 1, and is designated as polyamide 66 carbon black masterbatch-8. The yarn produced using the polyamide 66 carbon black masterbatch-8 provided in the comparative example is designated as nylon 66 black yarn-8.

[0045] Comparative Example 7 The nylon 66 carbon black masterbatch comprises the following components by weight percentage: 68.3% polyamide 66 semi-dull chips, 30.0% nano-sized carbon black powder, and 1.7% single-type superdispersant. The masterbatch production process is the same as in Example 1, and is designated as polyamide 66 carbon black masterbatch-9. The yarn produced using the polyamide 66 carbon black masterbatch-9 provided in the comparative example is designated as nylon 66 black yarn-9. Comparative Example 8 The nylon 66 carbon black masterbatch comprises the following components by weight percentage: 68.0% polyamide 66 semi-dull chips, 30.0% nano-sized carbon black powder, and 2.0% single-type superdispersant. The masterbatch production process is the same as in Example 1, denoted as Polyamide 66 Carbon Black Masterbatch-10. The yarn produced using the polyamide 66 carbon black masterbatch-10 provided in the comparative example is denoted as Nylon 66 Black Yarn-10.

[0046] Comparative Example 9 Except for changing the raw material to 100% polyamide 66 semi-dull chips, the other process conditions are the same as in Example 4, and the resulting yarn is denoted as nylon 66 white yarn.

[0047] Performance testing Figure 1 The image shows a physical picture of the high-strength, low-elongation nylon 66 carbon black masterbatch prepared by the method provided in this invention. The high-strength, low-elongation nylon 66 carbon black masterbatch is in the form of cylindrical granules.

[0048] The physical property test results of the nylon 66 carbon black masterbatch prepared according to Examples 1-3 and Comparative Examples 1-8 are shown in Table 1.

[0049] Table 1 Comparison of physical property data of Nylon 66 carbon black masterbatch

[0050] Note: Because masterbatch could not be obtained in Comparative Implementation 2, it is not listed. 3. The finished products prepared in Examples 4 to 6 and Comparative Examples 1 to 9 were subjected to performance tests. The comparison of the use of nylon 66 carbon black masterbatch in spinning and the corresponding physical properties is shown in Table 2, and the color comparison is shown in Table 3.

[0051] Table 2 Comparison of physical properties of 60D / 24F nylon 66 black yarn and white yarn

[0052] Table 3. Comparison of color measurement data between 60D / 24F Nylon 66 black yarn and white yarn

[0053] Comparison of spinning conditions and physical properties revealed that, after dispersant screening and ratio optimization, the nylon 66 carbon black masterbatch produced using 1.2-1.5% of the single-type modified superdispersant ABX01 and 0.2-0.3% of the high-temperature resistant antioxidant, under the same spinning conditions, produced nylon 66 black yarn-1 with higher breaking strength and lower breaking elongation. Furthermore, the spinning cycle of the components was longer, and the average daily breakage rate was lower. This indicates that the carbon black in the 30% carbon black content nylon 66 carbon black masterbatch produced by this formula has better dispersibility. This further verifies that the polyamide structure in the dispersant can better bind with nylon 66. The added long-chain branches and functional groups of the modified fatty acids increase steric hindrance, achieving multi-point anchoring and three-dimensional protection, reducing carbon black agglomeration, and enabling this dispersant to achieve high efficiency with minimal dosage, thus reducing the final amount of dispersant used. Meanwhile, the addition of high-temperature resistant antioxidants effectively alleviates the problems of decreased breaking strength and increased breaking elongation caused by thermal oxidative degradation of polyamide 66 chips in high-temperature environments during masterbatch production and spinning.

[0054] Meanwhile, the nylon 66 black yarn produced using the carbon black masterbatch of nylon 66 produced by this invention shows higher blackness as indicated by the color measurement results in Table 3. This further proves that the combined effect of the modified dispersant and the high-temperature antioxidant determined after screening enables the carbon black in the masterbatch to have better dispersibility, while alleviating the self-oxidative degradation of polyamide 66 chips caused by the high-temperature processing environment.

[0055] The above description is only a preferred embodiment of the present invention. It should be noted that those skilled in the art can make several modifications and improvements without departing from the inventive concept of the present invention, and these all fall within the protection scope of the present invention.

Claims

1. A high-strength, low-elongation nylon 66 carbon black masterbatch, characterized in that, Includes the following components by weight percentage: It contains 68.2%–68.8% polyamide 66 chips, 30% nano-sized carbon black powder, 1%–1.5% single-type modified superdispersant and 0.2%–0.3% high-temperature resistant antioxidant.

2. The high-strength, low-elongation nylon 66 carbon black masterbatch according to claim 1, characterized in that, The polyamide 66 chips are one of glossy polyamide 66 chips, semi-matte polyamide 66 chips, or fully matte polyamide 66 chips.

3. The high-strength, low-elongation nylon 66 carbon black masterbatch according to claim 1, characterized in that, The polyamide 66 chips have a water content of 600–1000 ppm, an extractable content of ≤0.3%, a molecular weight of 18,000–28,000, and a relative viscosity of 2.45–2.

70.

4. The high-strength, low-elongation nylon 66 carbon black masterbatch according to claim 1, characterized in that, The nano-sized carbon black powder has a particle size of 30–50 nm and an oil absorption value ≤70 cm⁻¹. 3 / 100g, purity ≥99.99%.

5. The high-strength, low-elongation nylon 66 carbon black masterbatch according to claim 1, characterized in that, The single-type modified superdispersant is a polyamide dispersant with a melting point in the range of 140-160℃ and a thermal decomposition degree of ≤97% at 300℃.

6. The high-strength, low-elongation nylon 66 carbon black masterbatch according to claim 1, characterized in that, The high-temperature resistant antioxidant is a compound of A30 antioxidant and S9228 antioxidant, wherein the compounding ratio is A30:S9228, (1~2):

1.

7. A method for preparing a high-strength, low-elongation nylon 66 carbon black masterbatch according to any one of claims 1-6, characterized in that, Specifically, the following steps are included: S1. Premix nano-sized carbon black powder with a single type of modified superdispersant to obtain a uniform mixture; S2. The polyamide 66 chips are automatically fed through the main feed port at a set flow rate; the mixture from step S1 is fed through the side feed port at a set flow rate. S3, the mixture, and polyamide 66 chips were sequentially processed in a parallel co-rotating twin-screw extruder through melt plasticization, screw conveying and shearing, water-cooled pelletizing, vibration screening, and forced-air drying to prepare high-strength, low-elongation nylon 66 carbon black masterbatch.

8. The preparation method according to claim 7, characterized in that, The melting and plasticizing process is divided into eleven temperature zones and a die head temperature zone, with the temperature controlled within the range of 250 to 280°C.

9. The application of a high-strength, low-elongation nylon 66 carbon black masterbatch in black yarn spinning, characterized in that: The high-strength, low-elongation nylon 66 carbon black masterbatch described in claim 1 is melt-blended and spun with polyamide 66 chips at a spinning temperature of 280–300°C, a die temperature of 280–295°C, and a draw ratio of 1.3–1.6.

Citation Information

Patent Citations

  • Carbon black master batch for chinlon 6 civil filament fiber as well as preparation method and application of carbon black master batch

    CN113321929A